The Belt and Road Initiative: Chinese plan of global economic governance - Haoxiang Ren (2019)
After World War II, traditional powers declined, the United States became the only superpower in the world. Based on its judgments and considerations of the international economic situation at that time, the United States promoted the establishment of the UN, IMF, WB, GATT, WTO and other organizations. In this context, international economic and political rules and systems centering on the interests of the West and the United States have been gradually established. It is undeniable that this governance system has played a certain role, which has contributed greatly to the overall peace, stability and sustainable development of the world after World War II. However, after more than 60 years of development and evolution, especially after the impact of the end of the cold war, the global governance system formed at the end of World War II is increasingly difficult to adapt to the development of the world, and even gradually become the shackles of world development. In a sense, the international financial crisis triggered by the United States in 2008 can also be regarded as the outbreak of the contradictions caused by the old international economic and political order. It has been more than ten years since the outbreak of the international financial crisis, but the deep shock of the global economy caused by it has not yet completely faded. At present, global economic governance faces many difficulties. On the one hand, the United States has withdrawn from the Paris Agreement and the TPP, promoted the US priority policy. The EU has also been riddled with many internal events such as the BREXIT and the refugee crisis. In this context, the global economic recovery is full of uncertainties. On the other hand, the economic growth of emerging countries and developing countries is obvious, and gradually become a new focus for leading the global economic development. In the process, China has also become an important active force in economic globalization and plays an increasingly important role in global economic governance. In this context, the construction of the BRI has effectively promoted the economic development of China and the countries along the route. The principle of “extensive consultation, joint contribution and Shared benefits” advocated by the BRI is profoundly changing the global economic order. As a Chinese scheme of global economic governance, it has become an innovative measure for China to participate in global economic governance.